Revolutionizing Students' Success: The Dynamic Impact of Cultural-Techno-Contextual Approach on Academic Achievement in Difficult Concepts in Senior Secondary Chemistry - OLUSEGUN, Bisola Esther; SAIBU, Sakibu Olajide; ALAKA, Michael Olusegun; OLUDE, Adebisi Sylvester (Ilorin Journal of Education, 2024)
This study investigated the impact of Culturo-Techno-Contextual Approach on students’ academic achievement in difficult chemistry concepts. A sequential explanatory mixed method involving a combination of quantitative and qualitative approaches was adopted. The quantitative approach involved a pre-test, post-test, non-equivalent control group quasi experimental design while the qualitative approach involved interview with a sample of 150 senior secondary school year two chemistry learners drawn from three randomly sampled senior secondary schools in Educational District V of Lagos State. Treatment consisted of teaching two difficult chemistry concepts to the experimental groups using culturo-techno-contextual approach while the control group was taught using the traditional lectured method. The research was carried out for eight weeks. Chemistry Achievement Test (CAT) and Interview Guide were used for the data collection after subjected to both content and face validity with the reliability established using K-20 to yield a coefficient of 0.87. The null hypotheses were tested using Analysis of Covariance (ANCOVA) at 0.05 level of significance. Results revealed that learners taught using culturo-techno-contextual approach performed significantly better than those taught by the traditional lecture method [F(1,147)=17.46; p<.05]. Also, no significant gender difference existed between performance of students taught using culturo-techno-contextual approach and those taught using the traditional lecture method [F(1,145)=.31; p>0.05]. Based on the findings of the study as well as the feedback from the interview guide, it was recommended among others that teachers should adopt culturo-techno-contextual approach as an innovative strategy for teaching chemistry to students in senior secondary schools.